The Solid-state Isomerization of cis and trans-(η5 -C5H4Me)Mo(CO)2(P(Oi Pr)3)I - Olalere G. Adeyemi (My University, 2002)
The cis- and trans-(η5 -C5H4Me)Mo(CO)2(P(Oi Pr)3)I complexes undergo a bi-directional thermal ligand isomerization reaction to yield an equilibrium mixture of isomers (30/70 cis/trans ratio, 90 °C, < 80 min) in the solid state. The activation energy barrier for the cis-trans isomerization reaction (80–100 °C) was found to be 68 ± 10 kJ mol–1. In benzene (reflux, 2 h) this isomer ratio was found to be 70:30 cis/trans. DSC and powder XRD studies have revealed reactions that occur in the solid state entailing decomposition and isomerization. DSC experiments did not reveal the presence of the cis–trans isomerization reaction.
Keywords: Isomerization/ solid state / XRD powder diffraction / molybdenum